2010
DOI: 10.1088/0031-9155/56/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Tapered LSO arrays for small animal PET

Abstract: By using detectors with good depth encoding accuracy (~ 2 mm), an animal PET scanner can be built with a small ring diameter and thick crystals to simultaneously obtain high spatial resolution and high sensitivity. However, there will be large wedge-shaped gaps between detector modules in such a scanner if traditional cuboid crystal arrays are used in a polygonal arrangement. The gaps can be minimized by using tapered scintillator arrays enabling the sensitivity of the scanner to be further improved. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
(53 reference statements)
0
50
1
Order By: Relevance
“…29 There is a growing trend of going toward finer crystal pixelation to improve spatial resolution, specifically in preclinical or dedicated brain PET systems. 5,[30][31][32][33] Using radially long scintillation crystals to maximize the detection sensitivity of the PET camera increases the parallax error 34,35 and degrades the system's spatial resolution, 28 especially at trans-axial distances far from the center field of view (FOV). Additionally, by accepting bigger ring differences for coincident events along the axial FOV, the parallax error causes distortions in the reconstructed image.…”
Section: Introductionmentioning
confidence: 99%
“…29 There is a growing trend of going toward finer crystal pixelation to improve spatial resolution, specifically in preclinical or dedicated brain PET systems. 5,[30][31][32][33] Using radially long scintillation crystals to maximize the detection sensitivity of the PET camera increases the parallax error 34,35 and degrades the system's spatial resolution, 28 especially at trans-axial distances far from the center field of view (FOV). Additionally, by accepting bigger ring differences for coincident events along the axial FOV, the parallax error causes distortions in the reconstructed image.…”
Section: Introductionmentioning
confidence: 99%
“…The computational cost using the LORI method can be significantly reduced without compromising image quality; furthermore, it provides good insights into collimated PET. Finally, the collimated PET method can mitigate the technical difficulties of manufacturing extremely small crystals with extremely high cost (Yang et al 2011), and it may open a new dimension to improve spatial resolution in small-animal and human PET imaging applications.…”
Section: Discussionmentioning
confidence: 99%
“…The most direct method is to reduce the crystal size (i.e. increase the number of crystals per unit area) by scintillator manufacturing techniques (Cherry et al 1997, Miyaoka et al 2001, Yang et al 2011). The reduction in crystal size can effectively improve the spatial resolution; however, it may not be cost effective with current manufacturing processes and it leads to increased inter-crystal scatter.…”
Section: Introductionmentioning
confidence: 99%
“…In many other studies, it has been shown that a diffuse reflector generally provides superior DOI resolution. 22,23 Second, mispositioned events will introduce greater DCI uncertainty as each crystal displays a unique DCI vs DOI relationship. Finally, beam broadening and intercrystal scatter with side-on measurements will introduce blurring of DOI metrics.…”
Section: Head-on (%)mentioning
confidence: 99%